Using mobiles in early childhood and elementary settings - Visser, Ryan (Digital media and learning, 2020)
"Mobile learning is a primary learning format in the education of young children (defined as from birth through 6th grade for the purpose of this book). Mobile learning has been found to have a positive impact on the academic achievement, self-efficacy, motivation, learning attitudes of students, including those with special needs (Ciampa, 2014; Hwang, 2014; Nikou & Economides, 2018; Xie, Basham, Marino & Rice, 2018). In both formal and informal learning contexts, mobile learning affords opportunities to innovate and explore new forms of authentic experiences, meaning-making and creativity with untethered technology (Choi, Land, & Zimmerman, 2018; Schuck, Kearney & Burden, 2017). This edited book acts as a springboard to expand discussions surrounding how mobiles might best be situated in contexts relating to young children. Due to the focus on early childhood and elementary settings, the definition of mobiles can be expanded to encompass digital-physical tools (e.g. Osmo, probeware) and wearables. This edited book provides educational researchers, teacher educators, teachers, and other stakeholders with an opportunity to share studies and/or experiences that explore the integration of mobiles and mobile learning into early childhood and elementary settings. More specifically, we encourage work that spans formal and informal learning experiences, innovative and traditional uses of technology for teaching and learning, community to school connections, and school and state initiatives. We encourage chapters that respond to the following questions: How have mobiles influenced early childhood and/or elementary educational practices and settings? What is the relationship between mobile learning and other school, district, state, and/or national initiatives? How does the school infrastructure promote or inhibit the use of mobiles in early childhood and elementary settings? How do various initiatives (e.g., 1:1, Bring Your Own Device) support students' intuitive use of mobiles for academic use? What cultural and/or community practices influence the connection and transfer of mobiles to academic settings? How has mobile learning been viewed and used as a practice for supporting multiple domains of development? In what ways do access, equity, and culture influence how/why mobiles are or are not being used in birth to 6th grade settings? What implications do mobile learning initiatives have for teacher education programs and professional development experiences? How are institutions of higher education preparing future early childhood and elementary educators for mobile-friendly environments?"--